Correlation of Interleukin-6 Level with Neutrophil to Lymphocyte Ratio and Disease Severity in COVID-19 Patients - Apriningsih, Hendrastutik; Prabowo, Nurhasan Agung; Reviono, Reviono; Anindita, Brigitta Devi; Myrtha, Risalina; Putri, Desy Puspa; Hermawati, Berty Denny (Universitas Islam Bandung, 2023)
Coronavirus disease 2019 (COVID-19) causes severe acute respiratory disease in humans and has spread rapidly worldwide since its first identification in December 2019. The neutrophil-to-lymphocyte ratio (NLR) describes the balance between the severity of inflammation and the immune system to be used as an important systemic inflammatory marker. Rapid progression of clinical deterioration is characterized by severe respiratory symptoms related to high levels of pro-inflammatory cytokines, like interleukin-6 (IL-6), indicating that the occurrence of cytokine storms leads to increased mortality. This study aims to assess the correlation between IL-6 and NLR in predicting the severity of COVID-19. This prospective cohort study was conducted at the COVID-19 ward of Universitas Sebelas Maret Hospital in August–September 2021. This study involved 66 COVID-19 patients >18 years old with asymptomatic to critical degree and Charlson Comorbidity Index (CCI) value ≤3. Examination of laboratory parameters and serum IL-6 was carried out when the patient entered the Emergency Room. Statistical test with Pearson’s correlation test, significant if p<0.05. There is no significant correlation between IL-6 and NLR with p=0.56 and r=0.08, and a strong correlation between IL-6 and disease severity with p=0.000 and r=0.454. The conclusion is that IL-6 does not correlate with NLR and strongly correlates with disease severity in COVID-19 patients.